Integrated investigation of the prognostic role of HLA LOH in advanced lung cancer patients with immunotherapy - Zhang, Xiaotao; Tang, Hongzhen; Luo, Haitao; Lu, Huiping; Pan, Chaohu; Yu, Haiming; Zhang, Linlin; Guan, Yaping; Yu, Lan; Chu, Huili; Chen, Jun; Wang, Jun (Frontiers in Genetics, 2022)
Although multiple studies have shown that loss of heterozygosity (LOH) at the human leukocyte antigen (HLA) locus is one of the mechanisms of immune escape, the effect of HLA LOH on the immunotherapy response of patients is still unclear. Based on the data of 425 Chinese lung cancer patients treated with anti-PD-L1 antibodies, the genomic characteristics with different HLA LOH statuses were analyzed. The driver genes mutation frequency, oncogenic signaling pathways mutation frequency, tumor mutational burden (TMB) and chromosomal instability (CIN) score in the HLA LOH high group was significantly higher than in the HLA LOH negative group. Transcriptome analyses revealed that pre-existing immunologically active tumor microenvironment (TME) was associated with HLA LOH negative patients. NSCLC patients, especially for lung squamous cell carcinomas (LUSC), with HLA LOH negative have a longer survival period than those with HLA LOH. In addition, the combination of HLA LOH with TMB or PD-L1 expression can further distinguish responders from non-responders. Furthermore, a comprehensive predictive model including HLA LOH status, TMB, PD-L1 expression and CD8+ T cells was constructed and exhibited a higher predictive value, which may improve clinical decision-making.